Perencanaan Pembangunan (E-Musrenbang ) Dengan Menggunakan Metode Importance Performance Analysis ( IPA ) Di Kota Surabaya - Nuraini Kusuma Andriyani; Sri Juni Woro Astuti (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2019)
This study aims to find out whether there are gaps between expectations and reality that are felt by the community using the e-musrenbang service system, using the Importance Performance Analysis (IPA) method. The E-musrenbang system is one of the public policy innovations in the field of development planning carried out by the Surabaya City Development Planning Agency. Through e-musrenbang, citizens can check what activities have been proposed and the status of their approval. As an innovation, the quality of e-musrenbang services needs to be evaluated. The indicators used include six variables, namely the quality system, information quality, service quality, user, user satisfaction, and net benefits. Respondents in this study were users of e-musrenbang which included 25 RW heads, and officials in 4 sub-districts which were densest in 1 sub-district, namely Benowo sub-district in Surabaya city area. The results of descriptive statistical tests that compare the performance and expectations of respondents obtained results from 6 indicators, the highest level of expectations is found in the indicator of service quality, while the lowest expectation lies in the user indicator. This causes the indicator of "service quality" which consists of tangibles, responsiviness, security, acess, and understanding the customer is the most important factor for the user in the service of the E-Musrenbang system. Conversely, the indicator "user" especially "needs" is the least important. Overall the results of the comparison between service quality and community expectations of E-Musrenbang services in the city of Surabaya have gaps - 150.16.